2014
DOI: 10.1016/j.pec.2014.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Associations between patient–provider communication and socio-cultural factors in prostate cancer patients: A cross-sectional evaluation of racial differences

Abstract: Objective To examine the association between socio-cultural factors and patient-provider communication and related racial differences Methods Data analysis included 1854 men with prostate cancer from a population-based study. Participants completed an assessment of communication variables, physician trust, perceived racism, religious beliefs, traditional health beliefs, and health literacy. A multi-group structural equation modeling approach was used to address the research aims. Results Compared with Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 42 publications
2
38
0
Order By: Relevance
“…Overwhelming evidence, little of which represents AA experiences, suggests that decision making and decisional conflict for patients with serious illnesses and their families are impacted by factors including knowledge about diagnosis, treatment options, treatment outcomes, and information received from HCPs. [33][34][35][36][37][38] Communication is a critical component of end-of-life decision making among AAs and their families. 39 The findings from several studies suggest that AAs have limited knowledge a Missing values were due to family members' refusals or lack of knowledge to answer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overwhelming evidence, little of which represents AA experiences, suggests that decision making and decisional conflict for patients with serious illnesses and their families are impacted by factors including knowledge about diagnosis, treatment options, treatment outcomes, and information received from HCPs. [33][34][35][36][37][38] Communication is a critical component of end-of-life decision making among AAs and their families. 39 The findings from several studies suggest that AAs have limited knowledge a Missing values were due to family members' refusals or lack of knowledge to answer.…”
Section: Discussionmentioning
confidence: 99%
“…The former finding is consistent with another study where AAs' quality of communication was positively associated with religious beliefs. 36 In addition to measuring religious beliefs and quality of communication, these investigators measured AAs' trust in HCPs and found that AAs' trust in HCPs was positively associated with their quality of communication with HCPs. 36 Stronger religious values have been associated with greater trust in HCPs; trust, in turn, has been associated with higher quality of communication with HCPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Access to quality health care is not easily attained, and health insurance might be limited or unavailable (Miller, Kirk, Kaiser, & Glos, 2014; Thakur et al, 2014). Issues that are related to health literacy (Coughlin, Matthews-Juarez, Juarez, Melton, & King, 2014; Guo et al, 2014; James, Harville, Efunbumi, & Martin, 2014; Song et al, 2014) and cultural relevance (Coughlin et al, 2014; Craig et al, 2014) during the clinical encounter and decision-making processes (Smedley, Stith, & Nelson, 2003; United States Department of Health and Human Services Mental Health-The Office of Minority Health, 2016) might also be compromised.…”
Section: Introductionmentioning
confidence: 99%